Strategi pendidikan mitigasi bencana berbasis masyarakat: memperkuat kapasitas lokal untuk menghadapi perubahan iklim di Indonesia - rasidi rasidi (Universitas Muhammadiyah Magelang, 2024)
This study aims to understand community-based disaster mitigation strategies in Indonesia in the face of climate change. The research was conducted in Magelang Regency, Central Java, Indonesia, using a qualitative approach with a case study. The findings of the study show that the people of Magelang Regency have a high level of awareness of the threats of natural disasters and the impacts of climate change. However, their knowledge of mitigation and adaptation strategies still needs to be improved. The people of Magelang also have valuable local capacities, such as local knowledge, strong social networks, and mobilizable human resources. Mitigation strategies that have been implemented by the people of Magelang include awareness campaigns, infrastructure development, and the implementation of traditional practices. The findings of this study have several policy and practical implications. First, it is important to increase investment in educating and raising public awareness about disasters and climate change. Second, it is also necessary to improve public access to adequate disaster preparedness infrastructure. Third, community empowerment is needed to increase their active participation in disaster mitigation. Fourth, cooperation between the government, NGOs, the private sector, and local communities needs to be strengthened.